IMPLEMENTASI DAN MAKNA KEGIATAN PESANTREN KILAT DALAM MENINGKATKAN NILAI-NILAI KEAGAMAAN PESERTA DIDIK DI SMP NEGERI 3 BLORA - Muhammad Isnario Andrian; Muhammad Nabil; Muhammad Zainal Abidin (TA'LIM : Jurnal Studi Pendidikan Islam, 2026)
This study aims to describe the implementation and significance of pesantren kilat in enhancing students’ religious values at SMP Negeri 3 Blora. The research employed a descriptive qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using Miles and Huberman’s interactive model. The findings indicate that pesantren kilat was implemented through structured planning, active involvement of Islamic education teachers and university students as facilitators, and evaluations based on student participation. From the students’ perspective, the program fostered greater discipline in worship, deeper understanding of Islamic morals, and stronger social awareness. From the viewpoint of teachers and school leaders, pesantren kilat functioned as a bridge between classroom-based religious theory and real-life practice. These results demonstrate that pesantren kilat is not merely a ceremonial activity but an effective educational strategy for the internalization of religious values. The study concludes that pesantren kilat contributes significantly to strengthening students’ religious character while also promoting social solidarity and spiritual growth within the school environment.